الحركات الاحتجاجية وأثرها على تعزيز سياقات التحول الديمقراطي في الوطن العربي (مصر- تونس - البحرين) - خليفة, حمزة; بارة, سمير (University of Eloued جامعة الوادي, 2022)
تناولت دراستنا هذه دورالحركات الاجتماعية في تحديد مسار التحول الديمقراطي بالمنطقة العربية من خلال موجة ثورات الربيع العربي،حيث تطرقناإلى خلفياتهاوتسلسل أحداثها والتعرض إلى نتائجها ومدى تاثيرها على مسارات التحول الديمقراطي،إلى جانب ذلك تناولنا تأثيرالحركات الإجتماعية على عمليةالتحول الديمقراطي في كل من أوروبا ودول أمريكا اللاتينية،لتوضيح التماثلات بينها وبين التجارب العربية، وهذا ما يتيح فهم أعمق لنفس متغير الدراسةمن خلال المقارنات واسعة النطاق بين الأقاليم الناجحة في التحول الديمقراطي والأقاليم المتعثر أو الأقاليم المغلقة إتجاه التحول،وهذا ما ساعدنا في فهم أسباب تعثر عملية التحول الديمقراطي بالمنطقة العربية Abstract Our study examined the role of protest movements in leading forward the change and democratic transformation in the Arab region during the past two decades, besides studying the process of democratization in light of what is known as the rise of the Arab Spring, and we also discussed the process of democratic transformation in Europe and Latin American countries, to clarify the similarities between them, to benefit from those experiences and an establishing general rules to follow in the process of change and its mechanisms, especially the role of social justice movements (protest) , because what matters to peoples and the government in achieving the political stability based on democratic foundations that allow everyone to participate In the conduct of public affairs of the country.
المجلد13 العدد2
Keywords: لحركات الا جتماعية،الحركات الاحتجاجية،التحول الديمقراطي ، الإصلاح السياسي ، الإستقرار السياسي; social movements،protest movements،Democratic transition, political reform, political stability.